Differences in the Grade of Inflammation in the Liver Tissues of Old White Female Mice (Mus Musculus) due to Weight Bearing and Non-Weight Bearing Exercise - Muhammad Alim Ananto; Irfiansyah Irwadi; Alphania Rahniayu (Journal of Global Research in Public Health, 2021)
Old age causes a decrease in quality of life. Exercise inhibiting the decline in quality of life, however exercise can cause oxidative stress that causes tissue injury including in the liver. There are two types of exercise, weight-bearing and non-weight bearing exercise. It is unknown the type of exercise causes the least injury. This study aimed to analyze the differences in the inflammatory response shown by the degree of inflammation in the liver tissue of old female white mice who performed weight-bearing and non-weight bearing exercise. Thirty-six mice (mus musculus) were divided into 3 groups, control group (12), weight-bearing treatment group (12) and non-weight bearing treatment group (12). The weight bearing treatment consisted of running for 30 minutes, while the non-weight bearing treatment consisted of swimming for 30 minutes. Euthanized on the last day of 4th week. Microscopic evaluation of the degree of inflammation of the liver tissue was carried out according to the Batts and Ludwig method. Statistical analysis used the Kruskal Wallis method to determine whether there were differences in the degree of liver inflammation between groups. Mean value of inflammation degree in control group: 1,50 ± 0.552. Mean value of inflammation degree in weight-bearing exercise group: 1,92 ± 0.515. Mean value of inflammation degree in non-weight bearing exercise group: 1,92 ± 0.669. The Kruskal Wallis statistical test showed the P value 0.139. The results showed that there was no significant difference in the degree of inflammation in the mice liver after receiving weight-bearing and non-weight-bearing exercise treatments.